On the Best Linear Approximation Method for Hölder Classes - Skorokhodov, D. S. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We find the exact values of one-dimensional linear widths for the Hölder classes of functions in the space C and the value of the best approximation of the Hölder classes of functions by a wide class of linear positive methods.